PENGARUH MOTIVASI, KEPRIBADIAN, PELATIHAN DAN KARAKTERISTIK PEKERJAAN TERHADAP KETERLIBATAN PEKERJAAN PEGAWAI DINAS KESEHATAN PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA KOTA TANJUNGPINANG - Herman Herman (Sekolah Tinggi Pariwisata Mataram, 2021)
This study aims to determine and analyze the influence of motivation, personality, training and job characteristics on the job involvement of employees at the Health Office for Population Control and Family Planning in Tanjungpinang City. The method chosen is quantitative research by distributing questionnaires. The sample of this study were all employees of the Health Office of Population Control and Family Planning in Tanjungpinang City, totaling 78 employees with the status of Civil Servants. The data analysis method used is descriptive analysis and multiple linear regression analysis, t test and F test. The results of this study show that simultaneously motivation, personality, training and job characteristics have a positive and significant effect on job involvement with a significance level of 0.000. Partial testing for the Motivation variable has a significant effect on Job Involvement with a significance level of 0.001, the Personality variable has a significant effect on Job Involvement with a significance level of 0.005, the Training Variable has a significant effect on Job Involvement with a significance level of 0.000 and Job Characteristics has a significant effect on Job Involvement with a significance level of 0.009